2007
DOI: 10.1021/jp070016c
|View full text |Cite
|
Sign up to set email alerts
|

Orientation-Resolving Pulsed Electron Dipolar High-Field EPR Spectroscopy on Disordered Solids:  I. Structure of Spin-Correlated Radical Pairs in Bacterial Photosynthetic Reaction Centers

Abstract: Distance and relative orientation of functional groups within protein domains and their changes during chemical reactions determine the efficiency of biological processes. In this work on disordered solid-state electron-transfer proteins, it is demonstrated that the combination of pulsed high-field EPR spectroscopy at the W band (95 GHz, 3.4 T) with its extensions to PELDOR (pulsed electron-electron double resonance) and RIDME (relaxation-induced dipolar modulation enhancement) offers a powerful tool for obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
136
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(143 citation statements)
references
References 50 publications
5
136
2
Order By: Relevance
“…From the angles obtained and a comparison with the X-ray structure, the authors conclude that the quinone undergoes a 60°rotation upon reduction. Examination of the angles obtained in Heinent et al (2007), however, shows that within experimental error the orientation of the dipolar coupling vector in the quinone g-tensor frame is the same as that given by the Xray structure and is also the same as that determined in Kandrashkin and van der Est (2001) and Savitsky et al (2007). Thus, the proposed 60°rotation of the quinone is about the dipolar coupling axis.…”
Section: Light-induced Structural Changessupporting
confidence: 51%
See 3 more Smart Citations
“…From the angles obtained and a comparison with the X-ray structure, the authors conclude that the quinone undergoes a 60°rotation upon reduction. Examination of the angles obtained in Heinent et al (2007), however, shows that within experimental error the orientation of the dipolar coupling vector in the quinone g-tensor frame is the same as that given by the Xray structure and is also the same as that determined in Kandrashkin and van der Est (2001) and Savitsky et al (2007). Thus, the proposed 60°rotation of the quinone is about the dipolar coupling axis.…”
Section: Light-induced Structural Changessupporting
confidence: 51%
“…Calculation of the quasi-static K-band (van der Est et al 1993) and W-band (Prisner et al 1995; Kandrashkin and van der Est 2001) TREPR spectra using the geometry from the X-ray structure are in good agreement with the experimental spectra, which suggests that any light-induced reorientation is small. Recently, two independent studies (Heinent et al 2007;Savitsky et al 2007) have re-examined this issue and made use of additional data to refine the comparison. Both studies found evidence for the reorientation of Q A upon reduction, but the nature of the reorientation is significantly different in the two articles.…”
Section: Light-induced Structural Changesmentioning
confidence: 99%
See 2 more Smart Citations
“…Orientation selection was analyzed for high-frequency DEER with enhanced symmetry of the relative orientation without (82) and with (83) conformational distribution of the paramagnetic center and for general symmetry for a cofactor pair in photosynthetic reaction centers (93). Analysis at X-band frequencies was desccribed for Cu 2+ -Cu 2+ (63, 94), Cu 2+ -nitroxide (63, 64) and iron-sulfur centre-nitroxide (94) pairs.…”
Section: Orientation Selectionmentioning
confidence: 99%